E-Module as Conflict Resolution: The Application of Pancasila Values in Analyzing Cases of Violation and Denial of Citizen Rights and Obligations - Angraini, Nosy Mutia; Suhono, Suhono; Dewi, Susi Fitria; Fatmariza, Fatmariza; Hidayah, Yayuk (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2022)
The conflict resolution e-module for KD is the relevance of applying the values of Pancasila in analyzing cases of violations and denial of the rights and obligations of citizens, in the subject of ENGLISH Students at Program Intensive Course at SMA class XII semester 1, serves as a practical learning medium for high school students to be able to understand and resolve conflicts. This study aims to assist students in recognizing various cases of violations and denial of the rights and obligations of citizens so that awareness of their rights and obligations as citizens can grow, with the hope of becoming good citizens who can avoid or manage conflicts well. This research is deliberately and systematically aimed or directed to be able to find or formulate products, models, media, methods, and certain strategies that are more effective, efficient and innovative. The research model used in This study is a Plomp research model which is an adaptation of the model developed by Tjeerd Plomyang. This model was chosen because it is more systematic, directed, suitable and relevant for the learning tools in the selected KD. The result show that learning using the E-Module Conflict Resolution as a learning medium for high school students or equivalent is declared more effective and practical. This is based on the comparative data obtained. Keyword: Conflict Resolution, E-Module Conflict Resolution, Pancasila Value